High-crack-resistance and high-performance concrete for tunnel as well as preparation method and application thereof
By using a high-performance concrete composed of cement, quartz sand, fly ash, silica fume, fiber, nanozirconia, etc. in tunnel engineering, the existing concrete is easily cracked and has low strength, and the performance requirements of high compression, flexural and crack resistance are achieved.
Patent Information
- Application Number
- CN202411956259.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-03-28
AI Technical Summary
Existing concrete is prone to cracking and has low strength in tunnel projects, making it difficult to meet the safety and stability needs of tunnel structures.
A high-performance concrete composed of cement, quartz sand, fly ash, silica fume, fiber, nanozirconia, etc. is used to enhance the crack resistance and strength of the concrete through the combination of polyamide fiber and basalt fiber, as well as the surface modification of nanozirconia by polytetrafluoroethylene emulsion.
It significantly improves the compressive, flexural strength and crack resistance of concrete, and can meet the high requirements for concrete performance in tunnel engineering.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of concrete, and in particular to a high-crack-resistant and high-performance concrete for tunnels, and a preparation method and application thereof. Background Art
[0002] With the rapid development of modern transportation infrastructure construction, the number of tunnel projects is increasing and the scale is expanding. Tunnels face many challenges in operation, such as complex and changeable geological conditions, high water pressure, frequent vehicle vibrations, and long-term environmental erosion. Against this background, the market has put forward extremely high performance requirements for concrete materials used in tunnel construction, especially in terms of crack resistance and strength. At present, commercially available concrete still has the problems of easy cracking and low strength, which is not conducive to ensuring the safety and stability of tunnel structures, and may even affect the normal use of tunnels. Therefore, it is of great significance to develop a high-crack-resistant and high-performance concrete for tunnels. Summary of the invention
[0003] The present invention provides a high-crack-resistant and high-performance concrete for tunnels, and a preparation method and application thereof, which solve the problems of easy cracking and low strength of concrete in related technologies.
[0004] The technical solution of the present invention is as follows: The invention provides a high-crack-resistant and high-performance concrete for tunnels. The raw materials include the following components in parts by weight: 70-100 parts of cement, 80-90 parts of quartz sand, 60-80 parts of fly ash, 30-40 parts of silica fume, 20-30 parts of fiber, and 10-20 parts of nano zirconium oxide.
[0005] As a further technical solution, the fiber is a composite fiber with a mass ratio of polyamide fiber to basalt fiber of 1:3-4.
[0006] In the present invention, the combination of polyamide fiber and basalt fiber can further enhance the crack resistance and strength of concrete, and when the mass ratio of polyamide fiber to basalt fiber is 1:3-4, the crack resistance and strength of concrete can be further enhanced.
[0007] As a further technical solution, the preparation method of the composite fiber is: heating and melting the polyamide fiber, adding the basalt fiber to mix, pulling, cooling and solidifying, to obtain the composite fiber.
[0008] In the present invention, the polyamide fiber is melt-mixed on the surface of the basalt fiber, which helps to further improve the crack resistance and strength of the concrete.
[0009] As a further technical solution, the nano zirconium oxide is polytetrafluoroethylene modified nano zirconium oxide.
[0010] In the present invention, the surface of nano zirconium oxide is modified by using polytetrafluoroethylene emulsion, thereby increasing the dispersibility of nano zirconium oxide, thereby further enhancing the crack resistance and strength of concrete.
[0011] As a further technical solution, the preparation method of the polytetrafluoroethylene modified nano zirconium oxide is: adding nano zirconium oxide to polytetrafluoroethylene emulsion, dispersing evenly, curing and grinding to obtain the polytetrafluoroethylene modified nano zirconium oxide.
[0012] As a further technical solution, the mass ratio of the polytetrafluoroethylene emulsion to the nano zirconium oxide is 1:4-7.
[0013] In the present invention, when the mass ratio of polytetrafluoroethylene emulsion to nano zirconium oxide is 1:4-7, it helps to further enhance the crack resistance and strength of concrete.
[0014] As a further technical solution, the particle size of the polytetrafluoroethylene modified nano zirconium oxide is 40-60 nm.
[0015] As a further technical solution, the particle size of the quartz sand is 1-3 mm, and the specific surface area of the fly ash is 600-700 m 2 / kg, the specific surface area of the silica ash is 20000~25000m 2 / kg.
[0016] As a further technical solution, the raw material further includes 2 to 4 parts of a water reducer, and the water reducer is a naphthalene-based water reducer or a polycarboxylic acid water reducer.
[0017] The present invention also proposes a method for preparing the high crack-resistant high-performance concrete for tunnels, comprising the following steps: mixing the components evenly, adding water and mixing until evenly mixed, to obtain the high crack-resistant high-performance concrete for tunnels.
[0018] The present invention also proposes the use of the high crack resistance and high performance concrete for tunnel or the high crack resistance and high performance concrete for tunnel obtained by the preparation method in tunnel engineering.
[0019] In the present invention, the high crack resistance and high performance concrete for tunnel can be used for tunnel lining or invert filling in tunnel engineering.
[0020] The working principle and beneficial effects of the present invention are: In the present invention, through reasonable component selection and proportioning, the concrete has good crack resistance and strength, which can meet the market performance requirements for concrete used in tunnel engineering. Among them, the added fiber can play a bridging role in the concrete matrix, while preventing cracks from expanding, it can also disperse stress and enhance the crack resistance and strength of the concrete; the added nano zirconium oxide can fill the tiny pores of the concrete, making the internal structure of the concrete more dense, thereby enhancing the crack resistance and strength of the concrete. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] In the following embodiments and comparative examples, unless otherwise specified, the type of cement is P·O 42.5R; the average particle size of quartz sand is 2 mm; the steel fiber is 446# steel fiber, with a diameter of 25 μm and a length of 1 mm; the type of polyamide fiber is TS272A1, with a diameter of 25 μm and a length of 1 mm; the diameter of basalt fiber is 25 μm, the length is 1 mm, the content of silicon dioxide is 43 wt %, the content of calcium oxide is 18 wt %, the content of magnesium oxide is 16 wt %, and the content of aluminum oxide is 12 wt %; the average particle size of nano zirconium oxide is 50 nm; the type of polytetrafluoroethylene emulsion is JF-4DCA; and the type of naphthalene water reducer is SZ211123.
[0023] Example 1 A method for preparing high crack resistance and high performance concrete for tunnels, comprising the following steps: mixing 70 parts of cement, 80 parts of quartz sand, and 60 parts of fly ash (with a specific surface area of 600 m 2 / kg), 30 parts of silica fume (specific surface area of 20000m 2 / kg), 20 parts of steel fiber, 10 parts of nano zirconium oxide and 2 parts of naphthalene-based water reducer are mixed evenly, and 20 parts of water are added and mixed until uniform to obtain high-crack-resistant and high-performance concrete for tunnels.
[0024] Example 2 A method for preparing high crack resistance and high performance concrete for tunnels, comprising the following steps: mixing 100 parts of cement, 90 parts of quartz sand, and 80 parts of fly ash (with a specific surface area of 700 m 2 / kg), 40 parts of silica fume (specific surface area of 25000m 2 / kg), 30 parts of steel fiber, 20 parts of nano zirconium oxide and 4 parts of naphthalene-based water reducer are mixed evenly, and 25 parts of water are added and mixed until uniform to obtain high-crack-resistant and high-performance concrete for tunnels.
[0025] Example 3 A method for preparing high crack resistance and high performance concrete for tunnels, comprising the following steps: mixing 100 parts of cement, 90 parts of quartz sand, and 80 parts of fly ash (with a specific surface area of 700 m 2 / kg), 40 parts of silica fume (specific surface area of 25000m 2 / kg), 30 parts of polyamide fiber, 20 parts of nano zirconium oxide and 4 parts of naphthalene-based water reducer are mixed evenly, and 25 parts of water are added and mixed until uniform to obtain high-crack-resistant and high-performance concrete for tunnels.
[0026] Example 4 A method for preparing high crack resistance and high performance concrete for tunnels, comprising the following steps: mixing 100 parts of cement, 90 parts of quartz sand, and 80 parts of fly ash (with a specific surface area of 700 m 2 / kg), 40 parts of silica fume (specific surface area of 25000m 2 / kg), 30 parts of basalt fiber, 20 parts of nano zirconium oxide and 4 parts of naphthalene-based water reducer are mixed evenly, and 25 parts of water are added and mixed until uniform to obtain high-crack-resistant and high-performance concrete for tunnels.
[0027] Example 5 A method for preparing high crack resistance and high performance concrete for tunnels, comprising the following steps: mixing 100 parts of cement, 90 parts of quartz sand, and 80 parts of fly ash (with a specific surface area of 700 m 2 / kg), 40 parts of silica fume (specific surface area of 25000m 2 / kg), 15 parts of polyamide fiber, 15 parts of basalt fiber, 20 parts of nano zirconium oxide and 4 parts of naphthalene-based water reducer are mixed evenly, and 25 parts of water are added and mixed until uniform to obtain high-crack-resistant and high-performance concrete for tunnels.
[0028] Example 6 A method for preparing high crack resistance and high performance concrete for tunnels, comprising the following steps: mixing 100 parts of cement, 90 parts of quartz sand, and 80 parts of fly ash (with a specific surface area of 700 m 2 / kg), 40 parts of silica fume (specific surface area of 25000m 2 / kg), 5 parts of polyamide fiber, 25 parts of basalt fiber, 20 parts of nano zirconium oxide and 4 parts of naphthalene-based water reducer are mixed evenly, and 25 parts of water are added and mixed until uniform to obtain high-crack-resistant and high-performance concrete for tunnels.
[0029] Example 7 A method for preparing high crack resistance and high performance concrete for tunnels, comprising the following steps: mixing 100 parts of cement, 90 parts of quartz sand, and 80 parts of fly ash (with a specific surface area of 700 m 2 / kg), 40 parts of silica fume (specific surface area of 25000m 2 / kg), 7.5 parts of polyamide fiber, 22.5 parts of basalt fiber, 20 parts of nano zirconium oxide and 4 parts of naphthalene-based water reducer are mixed evenly, and 25 parts of water are added and mixed until uniform to obtain high-crack-resistant and high-performance concrete for tunnels.
[0030] Example 8 A method for preparing high crack resistance and high performance concrete for tunnels, comprising the following steps: mixing 100 parts of cement, 90 parts of quartz sand, and 80 parts of fly ash (with a specific surface area of 700 m 2 / kg), 40 parts of silica fume (specific surface area of 25000m 2 / kg), 6 parts of polyamide fiber, 24 parts of basalt fiber, 20 parts of nano zirconium oxide and 4 parts of naphthalene-based water reducer are mixed evenly, and 25 parts of water are added and mixed until uniform to obtain high-crack-resistant and high-performance concrete for tunnels.
[0031] Example 9 A method for preparing high crack resistance and high performance concrete for tunnels, comprising the following steps: mixing 100 parts of cement, 90 parts of quartz sand, and 80 parts of fly ash (with a specific surface area of 700 m 2 / kg), 40 parts of silica fume (specific surface area of 25000m 2 / kg), 30 parts of composite fiber, 20 parts of nano zirconium oxide and 4 parts of naphthalene-based water reducer are mixed evenly, and 25 parts of water are added and mixed until uniform, to obtain high crack resistance and high performance concrete for tunnel; The composite fiber is prepared by heating and melting 6 parts of polyamide fiber, adding 24 parts of basalt fiber to mix, pulling, cooling and solidifying to obtain the composite fiber.
[0032] Example 10 A method for preparing high crack resistance and high performance concrete for tunnels, comprising the following steps: mixing 100 parts of cement, 90 parts of quartz sand, and 80 parts of fly ash (with a specific surface area of 700 m 2 / kg), 40 parts of silica fume (specific surface area of 25000m 2 / kg), 30 parts of composite fiber, 20 parts of polytetrafluoroethylene modified nano zirconium oxide and 4 parts of naphthalene series water reducer are mixed evenly, and 25 parts of water are added and mixed until uniform, so as to obtain high crack resistance and high performance concrete for tunnel; The composite fiber is prepared by heating and melting 6 parts of polyamide fiber, adding 24 parts of basalt fiber to mix, pulling, cooling and solidifying to obtain the composite fiber; The preparation method of polytetrafluoroethylene modified nano zirconium oxide is as follows: 15 parts of nano zirconium oxide are added to 5 parts of polytetrafluoroethylene emulsion, dispersed evenly, and solidified and ground to an average particle size of 50 nm to obtain polytetrafluoroethylene modified nano zirconium oxide.
[0033] Embodiment 11 The only difference between this embodiment and embodiment 10 is that the preparation method of polytetrafluoroethylene modified nano zirconium oxide in this embodiment is: add 18 parts of nano zirconium oxide to 2 parts of polytetrafluoroethylene emulsion, disperse evenly, solidify and grind to an average particle size of 50nm, and obtain polytetrafluoroethylene modified nano zirconium oxide.
[0034] Example 12 The only difference between this embodiment and embodiment 10 is that the preparation method of polytetrafluoroethylene modified nano zirconium oxide in this embodiment is: add 16 parts of nano zirconium oxide to 4 parts of polytetrafluoroethylene emulsion, disperse evenly, solidify and grind to an average particle size of 50nm, and obtain polytetrafluoroethylene modified nano zirconium oxide.
[0035] Embodiment 13 The only difference between this embodiment and embodiment 10 is that the preparation method of polytetrafluoroethylene modified nano zirconium oxide in this embodiment is: add 17.5 parts of nano zirconium oxide to 2.5 parts of polytetrafluoroethylene emulsion, disperse evenly, and solidify and grind to an average particle size of 50 nm to obtain polytetrafluoroethylene modified nano zirconium oxide.
[0036] Comparative Example 1 The only difference between this comparative example and Example 1 is that no steel fiber is added in this comparative example.
[0037] Comparative Example 2 The only difference between this comparative example and Example 1 is that nano zirconium oxide is not added in this comparative example.
[0038] The high crack resistance and high performance concrete for tunnels prepared in Examples 1 to 13 and Comparative Examples 1 to 2 were cured according to the curing method of the specimens in GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", and the curing age was 28 days. The following performance tests were performed on the cured concrete: ① Compressive strength: The compressive strength is measured according to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", where the specimen size is a 150mm cubic specimen and the loading speed is 0.8MPa / s; ② Flexural strength: The flexural strength was determined according to GB / T 50081-2019 “Standard for Test Methods for Physical and Mechanical Properties of Concrete”, where the specimen size was a prismatic specimen of 150mm×150mm×150mm, and the loading speed was 0.08MPa / s.
[0039] The total crack area per unit area of the high crack resistance and high performance concrete for tunnels prepared in Examples 1 to 13 and Comparative Examples 1 to 2 was measured according to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" 24 hours after pouring, wherein the specimen was a flat thin plate specimen of 800mm×600mm×100mm.
[0040] The test results are shown in Table 1 below.
[0041] Table 1 Test results of high crack resistance and high performance concrete for tunnels
[0042] It can be seen from the data in the table that the high crack resistance and high performance concrete for tunnels prepared by the present invention has high compressive and flexural strength, low total crack area per unit area, and can meet market demand. Comparison between Example 1 and Comparative Example 1 shows that the addition of steel fiber can significantly increase the crack resistance and strength of concrete. Comparison between Example 1 and Comparative Example 2 shows that the addition of nano zirconium oxide can significantly increase the crack resistance and strength of concrete.
[0043] By comparing Example 5 with Examples 2 to 4, it can be seen that the combination of polyamide fiber and basalt fiber can further enhance the crack resistance and strength of concrete. The comparison between Examples 5 to 6 and Examples 7 to 8 shows that when the mass ratio of polyamide fiber to basalt fiber is 1:3 to 4, the crack resistance and strength of concrete can be further enhanced. The comparison between Example 8 and Example 9 shows that by melt-mixing polyamide fiber on the surface of basalt fiber, it helps to further improve the crack resistance and strength of concrete.
[0044] The comparison between Example 9 and Example 10 shows that the surface modification of nano zirconium oxide by polytetrafluoroethylene emulsion can further enhance the crack resistance and strength of concrete. The comparison between Examples 12-13 and Examples 10-11 shows that when the mass ratio of polytetrafluoroethylene emulsion to nano zirconium oxide is 1:4-7, it helps to further enhance the crack resistance and strength of concrete.
[0045] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high crack resistance and high performance concrete for tunnels, characterized in that: The raw materials include the following components in parts by weight: 70-100 parts of cement, 80-90 parts of quartz sand, 60-80 parts of fly ash, 30-40 parts of silica fume, 20-30 parts of fiber, and 10-20 parts of nano zirconium oxide; The nano zirconium oxide is polytetrafluoroethylene modified nano zirconium oxide.
2. The high crack resistance and high performance concrete for tunnel according to claim 1, characterized in that: The fiber is a composite fiber with a mass ratio of polyamide fiber to basalt fiber of 1:3-4.
3. The high crack resistance and high performance concrete for tunnel according to claim 2, characterized in that: The preparation method of the composite fiber is: heating and melting the polyamide fiber, adding the basalt fiber to mix, pulling, cooling and solidifying to obtain the composite fiber.
4. The high crack resistance and high performance concrete for tunnel according to claim 1, characterized in that: The preparation method of the polytetrafluoroethylene modified nano zirconium oxide is as follows: adding nano zirconium oxide to polytetrafluoroethylene emulsion, dispersing evenly, and solidifying and grinding to obtain the polytetrafluoroethylene modified nano zirconium oxide.
5. The high crack resistance and high performance concrete for tunnel according to claim 1, characterized in that: The mass ratio of the polytetrafluoroethylene emulsion to the nano zirconium oxide is 1:4-7.
6. The high crack resistance and high performance concrete for tunnel according to claim 1, characterized in that: The particle size of the polytetrafluoroethylene modified nano zirconium oxide is 40-60 nm.
7. The high crack resistance and high performance concrete for tunnel according to claim 1, characterized in that: The raw materials also include 2 to 4 parts of a water reducer, and the water reducer is a naphthalene-based water reducer or a polycarboxylic acid water reducer.
8. A method for preparing high crack resistance and high performance concrete for tunnel according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing the components uniformly, adding water and mixing until uniform, and obtaining high-crack-resistant and high-performance concrete for tunnels.
9. Use of the high crack resistance and high performance concrete for tunnel according to any one of claims 1 to 7 or the high crack resistance and high performance concrete for tunnel obtained by the preparation method according to claim 8 in tunnel engineering.